Patients' experience and expectations of conservative management strategies, anti‐muscarinics and treatment with intravesical onabotulinum toxin for overactive bladder – a qualitative interview study. Issue 2 (20th May 2015) - Maguire, Turlough; Doshani, Angie; Mayne, Christopher; Slack, Mark; Tincello, Douglas
ABSTRACT: The RELAX trial studied the efficacy of intra‐detrusor onabotulinum toxin A (onaBoNTA) for the treatment of detrusor overactivity (DO) in women. Our objectives in this study were to explore patients' experience and understanding of taking part in a randomised controlled trial (RCT) and their experience of the treatment itself. In addition we explored how patients felt about their bladder problem prior to treatment, conservative management strategies they had been offered, and anti‐muscarinic treatment. Purposive sampling was used to interview patients who had successful and unsuccessful outcomes. Interviewers were blinded to this sampling. Semi‐structured telephone interviews were conducted with all recruited women. Analysis was using a grounded theory approach. Transcripts were analysed thematically based on a constant comparative method until the point of data saturation, that is no new themes were identified. Fifteen women in total were interviewed. There were eight global themes identified. These were: quality of life, conservative management, study awareness, reasons for participation, role of the media, the extension study, intervention and experience of a RCT. The impact of overactive bladder (OAB) symptoms was a strong theme leading to feelings of anxiety. All of the women interviewed perceived pelvic floor exercises as a short term plan. Compliance was sporadic and most discontinued because of lack of efficacy. All women had been counselled about the risk of voiding dysfunction after onaBoNTA treatment and women found the actual process of being taught clean intermittent self‐catheterisation by another woman difficult, Patients stated they felt embarrassed and traumatised by the experience. OnaBoNTA is an effective treatment for patients with DO whose disease burden is considerable. This work highlights the value of incorporating qualitative research methods into the design of RCTs particularly when dealing with surgical procedures.